The FOUR LEVERS OF CONTROL SEBAGAI LANDASAN SISTEM PENGENDALIAN STRATEGIS: KAJIAN LITERATUR SISTEMATIS - Putri Asilah (LP2M Politeknik Jambi, 2026)
This article examines the role of the Four Levers of Control as a foundational framework for strategic control systems through a structured review of relevant literature. By integrating Simons framework with strategic management accounting, contingency theory, and dynamic capabilities, this review analyses how organizations balance discipline, risk mitigation, and the need for continuous learning and innovation. Evidence from international and national studies shows that belief systems strengthen organizational purpose, boundary systems regulate acceptable behavior, diagnostic controls guide performance monitoring, and interactive controls support strategic dialogue and adaptation. The findings highlight that the effectiveness of strategic control does not rely on a single mechanism but on the integrated use of all four levers, tailored to organizational context and environmental conditions. This review provides a conceptual foundation that can support the development and refinement of strategic control practices across different organizational settings.